FREQUENCY OF OCULAR SYMPTOMS IN COVID-19 PATIENTS - Maria Zubair; Nida Hafeez; Wajeeha Rasool; Kanwal Zareen Abbasi; Ain Us Seher; Fuad A.K. Niazi (Journal of Rawalpindi Medical College)
Objective: To determine the frequency of ocular symptoms in COVID 19 patients and its association with systemic symptoms in active COVID 19 patients.